Distribution and sources of polycyclic aromatic hydrocarbons (PAHs) in surface sediment samples collected in South China Sea - Manan, Norazida (2012)
Petroleum pollution is one of the pollution that needs serious attention from world. Petroleum is worldwide used and introduced to aquatic environment through accidental oil spill, discharge from routine tanker operations. In other case, land based pollutants are contributed by rainfall and runoff waters. Polycyclic aromatic hydrocarbons (PAHs) are one of the major compounds in petroleum known as the most widespread organic pollutants. PAHs diagnostic rations applied in this study to identify the anthropogenic sources of PAH; petrogenic and pyrogenic. Thirty surface sediment samples were collected from South China Sea adjacent to the coast of Peninsular Malaysia using Ekcman Dredge sampler. The samples were extracted and fractionated prior to the analysis using gas chromatography- mass spectrometry (GC-MS) to quantify the concentration of PAHs. The total PAHs concentration of the marine sediment ranged from 0.0315x103 and 1.48x103 ng/g, dry weight. The concentration level of PAHs in the South China Sea is indicated as moderate to high contamination based on the global PAHs sedimentation records. Principal Component Analysis (PCA) in associated with Multiple Linear Regressions (MLR) has been performed to apportion PAHs sources in sediment samples. Seven factors and their percentages of contributions were identified based on PCA loadings of PAHs and were attributed to the following sources; (1) oil exploitation , 8.1%; (2) traffic emission, 43.8%; (3) road dust, 8.9%; (4) the spill of oil products, 3.6%; (5) unburned fossil fuels, 2.1%; (6) coal combustion, 10.2%; (7) oil combustion, 23.3%. The major source of anthropogenic PAHs pollution in the South China Sea is pyrogenic PAHs. This study should be conducted from time to time to monitor the concentration of PAHs in sediments.